Tradisi Songgot-Songgot Di Desa Aloban Bair : Kajian Tradisi Lisan - Yohana Dwikartika Hutabarat; Castia Stephani Sinaga; Eldawati Limbong; Dion Nardi Pangaribuan; Immanuel Silaban (Program Studi Magister Pendidikan Bahasa Indonesia FKIP Universitas Mataram, 2026)
The oral tradition of Songgot-Songgot among the Toba Batak people in Aloban Bair Village, Central Tapanuli, is a secret ritual known as mangupa/mangelek tondi, performed to restore the spirit following a disaster, including the flash flood of November 2025 that claimed 11 lives and triggered a trauma crisis, as well as the TNI’s piping project in April 2026. This qualitative study based on secondary data documents the 7 ritual stages (manggogot—scattering yellow rice and eggs; dekke nai arsik; mandok hata; tangiang; ulos Habonaran), symbolic meanings (reconstruction of the tondi; the duality of life and protection), and a 300% increase in frequency following the disaster. The findings confirm its effectiveness as communal psychospiritual therapy (85% recovery rate among victims), the assimilation of Protestant Christianity (97.65% of GKPI residents), and digital adaptation in the face of globalization and youth migration. Preservation strategies include audiovisual documentation, integration of trauma healing by the Social Services Department, indigenous school curricula, “Songgot Aloban” tourism (potential revenue of Rp500 million/year), and recommendations for a Central Tapanuli Regency Regulation. The research fills a gap in local linguistic anthropology, supports post-disaster policies, and revitalizes Batak Toba identity as a sustainable asset.